PENGEMBANGAN E-INSTRUMEN TWO-TIER MULTIPLE CHOICE BERBASIS HOTS TEMA AYO SIAGA BENCANA UNTUK MELATIH KEMAMPUAN BERPIKIR KRITIS SISWA KELAS VII - mutmainah, ilmia; Vitasari, Mudmainah; Biru, Lulu Tunjung (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2023)
The purpose of this study was to analyze the level of validity of the HOTS-based two-tier multiple choice e-instrument with the theme let's be prepared for disasters to train students' critical thinking skills in class VII. The method used in this study is Research and Development (R&D) with research and development steps according to Sugiyono (2014) which are limited according to the needs of researchers including potentials and problems, data collection, product design, product validation, product revision. The research instruments used were media expert questionnaire sheets, evaluation experts and science teacher experts to measure the validity level of the e-instrument. The results showed that the e-instrument expert validation carried out by the media expert validator obtained an assessment percentage of 80.68% in the "valid" category, the evaluation expert validation obtained a rating percentage of 97.80% in the "very valid" category, and expert validation science teachers get an assessment percentage of 97.77% in the "very valid" category. So if the average percentage value of the experts is calculated at 92.08% so that the validity level of developing a two-tier multiple choice e-instrument based on HOTS with the theme let's be prepared for disasters to train critical thinking skills for class VII students falls into the "very valid" category.